Journeys of Middle-Class Syrian Women to and in Berlin: Modes of Subjectivity, Possibilities and Becoming - Bashlah, Randa Adnan (AUC Knowledge Fountain, 2021)
This thesis is an invitation to dive into the possibilities that emerge in the multiple stages of displacement journeys of a group of diverse Syrian women from a middle-class background, who happen to live in Berlin today, and learn about the displaced bodies' experiences from a personal scale. By capturing the journeys' nuances and trajectories, this study demonstrates how the mobile subjects interact differently and create different attachments with different power structures in the various modes which emerge through the journeys' different spatial and chronological stages. Looking at how displacement adds layers of complexity to the social's messiness and diversity, this thesis provides an abundance of examples that display the fluidity and the leakages in the modern world hegemonic structures and refutes myths around refugees by examining the knowledge produced and reproduced in our modern world. Undoing categories such as the social, the refugee, and the contemporary form of citizenship invites future research that abstains from neat understandings of the messy realities and invites more thoughtfulness and creativity in examining these categories.